Promoting Interfaith Peaceful Coexistence among the People in Ekiti State - BUHARI Lateef Oluwafemi; Agus Suriadi; Syarifuddin (Britain International for Academic Research (BIAR) Publisher, 2024)
In recent times, Nigeria has been experiencing quite a number of turbulences among the various religons in the country. As a matter of fact, religious crisis is not new in the world. It is one of the most prominent among all conflicts that have faced mankind. History has it on record how religious conflicts had caused problems in the past of which an example was the crusade. This crisis in Nigeria has not only caused disruption to the economy, politics and social activities of the country internally, but has also cost the country its good image at the international level. The rate of religious crisis in Nigeria was what earned Nigeria the most terrorized country in the world after Afghanistan in 2019. Nonetheless, it is necessary to note that the rate at which these religious problems had been surfacing in the country also differs. In essence, certain locations in the country face religious problems more than others. Ekiti state among every other state in Nigeria only interact on few religious disparities since its creation in 1996. In Ekiti state, there have not been any open religious clashes between Christians and the Muslims unlike some other states in the country. This is as a result of the peaceful coexistence of the disciples of the different faiths in Ekiti. The leaders were urged to admonish their followers on the best way to promote understanding, harmony and cooperation among religions. The study relied heavily on numerous primary and secondary source materials including books, journal articles and other scholarly publications relevant to the study. It also benefited from the wealth of experience and insight of foremost traditional ruler, some clergymen from various churches, Islamic Scholars; academics, youths as well as members of the public.